Drivers of changing urban flood risk: A framework for action. (15th June 2019) - Berndtsson, R.; Becker, P.; Persson, A.; Aspegren, H.; Haghighatafshar, S.; Jönsson, K.; Larsson, R.; Mobini, S.; Mottaghi, M.; Nilsson, J.; Nordström, J.; Pilesjö, P.; et al.
Abstract: This study focuses on drivers for changing urban flood risk. We suggest a framework for guiding climate change adaptation action concerning flood risk and manageability in cities. The identified key drivers of changing flood hazard and vulnerability are used to provide an overview of each driver's impact on flood risk and manageability at the city level. We find that identified drivers for urban flood risk can be grouped in three different priority areas with different time horizon. The first group has high impact but is manageable at city level. Typical drivers in this group are related to the physical environment such as decreasing permeability and unresponsive engineering. The second group of drivers is represented by public awareness and individual willingness to participate and urbanization and urban sprawl. These drivers may be important and are manageable for the cities and they involve both short-term and long-term measures. The third group of drivers is related to policy and long-term changes. This group is represented by economic growth and increasing values at risk, climate change, and increasing complexity of society. They have all high impact but low manageability. Managing these drivers needs to be done in a longer time perspective, e.g., by developing long-term policies and exchange of ideas. Highlights: Decreasing permeability and unresponsive engineering mean high urban flood risk. Public awareness and urban sprawl have moderate impact on flood risk. Increasing values at risk and complexity of society also affect urban flood risk. Methods can be combined with a mixed expert and stakeholder participatory approach.